Glucoside derivative flexible liposome as well as preparation method and application thereof

Through the flexible liposome technology of glycoside derivatives that wrap bosein, phosphatidylcholine and polyquaternary ammonium salt-51 are used to improve the permeability and bioavailability of bosein, which solves its skin care The absorption efficiency and skin feel problem achieve significant anti-wrinkle firming effect and cost-effectiveness.

CN119235670AActive Publication Date: 2025-01-03SUZHOU MISIFU COSMETICS CO LTD

Patent Information

Application Number
CN202411769584.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Bose needs high additions to show anti-wrinkle firming effect in skin care products, but this leads to a decrease in absorption efficiency and poor skin feeling, and its penetration efficiency is low and its bioavailability is not high, making it difficult to achieve the expected transdermal penetration. Depth and target concentration.

Method used

The preparation method of glycoside derivative flexible liposomes is adopted, by wrapping bosein, phosphatidylcholine is used as the main shell material, polyquaternary ammonium salt-51 is used as the auxiliary shell material, butylene glycol is used as the moisturizing agent, 1, 2- Hexanediol, para-hydroxyacetophenone, hydroxybenzyl ester, caprylyglycol are used as preservatives, and deionized water is used as solvents to form liposomes with particle sizes of 10-40nm, improving their permeability and stability.

Benefits of technology

Improve the permeability and penetration depth of Bose, enhance its bioavailability on the skin, improve the skin's absorption efficiency and skin feeling, and reduce the amount of addition, thus achieving a more significant anti-wrinkle firming effect and cost-effectiveness. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119235670A_ABST
    Figure CN119235670A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of personal care, and particularly relates to a glycoside derivative flexible liposome and a preparation method and application thereof, the glycoside derivative flexible liposome comprises a main shell material, a humectant, a wrapped raw material, an auxiliary shell material, a preservative and a solvent; the main shell material is phosphatidylcholine, and the auxiliary shell material is polyquaternium-51; the preservative is any one or more of 1, 2-hexanediol, p-hydroxyacetophenone, methylparaben, phenoxyethanol and caprylyl glycol; the moisturizing agent is butanediol; the wrapped raw material is hydroxypropyl tetrahydrofurantriol; the solvent is deionized water. According to the invention, the permeability and penetration depth of the glassine and the concentration of the glassine at a target position are improved by utilizing a flexible liposome wrapping technology, the bioavailability of the glassine is improved, and the addition amount is reduced under the condition of realizing the same tightening and anti-wrinkle effects, so that the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of personal care, and specifically relates to a glycoside derivative flexible liposome and a preparation method and application thereof. Background Art

[0002] With age, the expression of glycosaminoglycans (GAGs) and proteoglycans (HS-PGs) in the extracellular matrix of the skin will gradually decrease, collagen in the skin will be lost, and the cohesion of the connecting layer between the epidermis and the dermis - the basement membrane layer (DEJ layer) will decrease, which cannot connect the epidermis and the dermis well, reducing the signal exchange and nutrient delivery between the epidermis and the dermis inside the skin, causing the skin to gradually age, develop wrinkles, and lose elasticity and firmness. Bosin (hydroxypropyl tetrahydrofurantriol) is an anti-aging active ingredient that targets the above three skin aging targets. It is a xylose derivative, composed of xylose and aglycone. Bosin can promote the expression of collagen I in the dermis and delay the loss of collagen in the skin. Bosin is also an activator of glycosaminoglycans, which can provide binding sites for the synthesis of glycosaminoglycans, promote the production of glycosaminoglycans, and further promote the production of proteoglycans. It has a promoting effect on three forms of proteoglycans - beaded proteoglycans, hyaluronic acid receptors (CD44) and adhesive proteoglycans. Glycosaminoglycans and proteoglycans (HS-PGs), which are important components of the extracellular matrix in the skin, can absorb a large amount of water, adhere to the surrounding cells, form elastic colloids, and support the fullness of the skin, thereby achieving the effects of anti-wrinkle and moisturizing.

[0003] In addition, Bosin can promote the synthesis of collagen VII and collagen IV. Collagen VII and collagen IV are located in the dermis-epidermis junction layer (DEJ layer), which can make the epidermis and dermis more closely connected, and enable the skin to better resist gravity and other mechanical stresses, making the skin firmer and more elastic.

[0004] Bose may promote the renewal of keratinocytes by activating growth factors and interacting with growth factors, and may also regulate epidermal homeostasis by releasing growth factors during skin aging. As a mild and effective anti-aging active ingredient, Bose is widely used in cosmetics, but some application pain points are also found in its application: 1. Bose needs to be added in sufficient amount to have a good anti-wrinkle and firming effect, but the high amount added leads to a decrease in absorption efficiency and poor skin feel; 2. Bose has low penetration efficiency and low bioavailability; 3. The main target of Bose for anti-wrinkle is located in the dermis-epidermal junction layer and the dermis. Under normal circumstances, the transdermal penetration depth and effective concentration of Bose at the target position are difficult to reach expectations, resulting in low bioavailability, slow anti-aging effect, and unclear anti-aging effect.

[0005] In response to the above-mentioned application pain points, there is an urgent need for a product that encapsulates phosphene that is stable, has a good skin feel, has a high transdermal absorption rate, has a high bioavailability, and can take into account both efficacy and cost, and is more cost-effective. Summary of the invention

[0006] The present invention aims at the deficiencies in the prior art and provides a glycoside derivative flexible liposome with moisturizing and anti-wrinkle functions and a preparation method and application thereof, which can improve skin roughness, smooth and delicate skin, and enhance the skin's absorption of active ingredients.

[0007] The present invention adopts the following technical solutions: A method for preparing a glycoside derivative flexible liposome, wherein the glycoside derivative flexible liposome comprises a main shell material, a moisturizing agent, a wrapped raw material, an auxiliary shell material, a preservative and a solvent; the main shell material is phosphatidylcholine; the auxiliary shell material is polyquaternium-51; the preservative is any one or more of 1,2-hexanediol, p-hydroxyacetophenone, methylparaben, phenoxyethanol and caprylyl glycol; the moisturizing agent is butylene glycol; the wrapped raw material is hydroxypropyltetrahydrofurantriol; and the solvent is deionized water; The preparation method comprises the following steps: heating the main shell material and the moisturizing agent to 45-75°C in a water bath and stirring evenly; then adding the wrapped raw material preheated to the same temperature and stirring evenly to obtain a mixture A; preheating the auxiliary shell material and the preservative to the same temperature, then adding them into the mixture A and continuously stirring to obtain a mixture B; after cooling, injecting the solvent into the mixture B, and continuously hydrating after the injection to obtain colostrum; homogenizing the colostrum to obtain a glycoside derivative flexible liposome, wherein the particle size of the glycoside derivative flexible liposome is 10-40nm; controlling the discharge temperature of the first homogenization to be 20-30°C, the discharge temperature of the second homogenization to be 15-25°C, and the discharge temperature of the third homogenization to be 10-20°C.

[0008] Furthermore, the glycoside derivative flexible liposome comprises the following components in parts by weight: 2-8 parts of a main shell material, 6-14 parts of a moisturizer, 25-35 parts of an encapsulated raw material, 0.3-3 parts of an auxiliary shell material, 1-2 parts of a preservative, and 38-65.7 parts of a solvent.

[0009] Furthermore, after obtaining the mixture B, the temperature is lowered to 35-45°C; and the solvent preheated to 35-45°C is injected into the mixture B.

[0010] Furthermore, the discharge temperature of the first homogenization pass is controlled to be 25°C, the discharge temperature of the second homogenization pass is controlled to be 20°C, and the discharge temperature of the third homogenization pass is controlled to be 15°C.

[0011] Furthermore, during the process of injecting the solvent into the mixture B, stirring is continued at a speed of 600-800 rpm, and hydration is continued for 15-25 minutes after the injection is completed to obtain colostrum.

[0012] Furthermore, the colostrum was homogenized using a high pressure homogenizer, the homogenization pressure was set to 12000-15000 psi, and the number of homogenization cycles was 3 times.

[0013] The present invention also provides a glycoside derivative flexible liposome prepared by the above method.

[0014] The present invention also provides the use of the above-mentioned glycoside derivative flexible liposome in personal care products.

[0015] Furthermore, the personal care product is a skin care product.

[0016] Furthermore, the mass percentage of the glycoside derivative flexible liposome in the personal care product is 1-3%.

[0017] Beneficial Effects

[0018] The glycoside derivative flexible liposome of the present invention is an efficient and mild moisturizing and anti-wrinkle raw material with excellent water-locking and moisturizing properties. It can form a breathable biofilm on the skin surface, simulate the stratum corneum to give the skin an extra layer of protection, reduce the stimulation of surfactants in skin care products, improve skin roughness, smooth and delicate skin, and enhance the skin's absorption of active ingredients.

[0019] Among them, the phospholipid raw materials used in the liposomes have certain moisturizing and antioxidant effects, good hydrophilicity and lipophilicity, and will increase skin luster after use. The flexible liposomes prepared with it as the main shell material have the advantages of low toxicity, high permeability and high skin compatibility, and can also bring better skin feel and promote the renewal and repair of skin cells.

[0020] Polyquaternium-51 is a copolymer composed of 2-methacryloylhydroxyethyl phosphatidylcholine and monomeric hydrophobic butyl methacrylate. It is a living body affinity raw material designed to mimic the cell membrane, which can inhibit the stimulation of various surfactants on living bodies and cells. Compared with ordinary polyquaternium salts, it has a unique bionic cell membrane structure and living body affinity. Polyquaternium-51 can form a stable hydrated gel film on the skin surface to lock in moisture and prevent moisture evaporation. It is a polymer moisturizer; at the same time, polyquaternium-51 has a cell membrane-mimicking structure, which can alleviate and inhibit the stimulation of surfactants on the skin. In addition to moisturizing and reducing surfactant stimulation, polyquaternium-51 also has many functions such as improving skin roughness, smoothing and delicate skin, and enhancing skin absorption of active ingredients.

[0021] The present invention innovatively uses polyquaternium-51 as a shell material, which is cationic and attracts the negative charge of skin cells, thereby facilitating penetration and absorption. It can also give the flexible liposomes better deformation ability, thereby achieving a penetration efficiency superior to that of general liposomes. Under non-enclosed conditions, the flexible liposomes are evenly applied to the skin, and the evaporation of the water therein will form a hydration penetration gradient from the outside to the inside on the skin surface, pulling the flexible liposomes to move along the pores into the skin, thereby increasing the transdermal absorption of the active substance.

[0022] Polyquaternium-51 cooperates with phospholipid raw materials and has good compatibility and stability. It can achieve the stability of phospholipids without adding external antioxidants such as sodium metabisulfite and vitamin E acetate.

[0023] The glycoside derivative flexible liposomes encapsulated by the preparation method of the present invention have good stability under high and low temperature conditions; the problems of decreased absorption efficiency and sticky skin feel caused by the high addition amount required for high anti-aging effect are solved; the permeability and penetration depth of bosera and the concentration at the target position are improved by using the encapsulation technology, the bioavailability of bosera is improved, and the addition amount is reduced while achieving the same firming and anti-wrinkle effect, thereby reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The particle size test data of Example 1 24 hours after preparation;

[0025] Figure 2 The appearance of Example 1 under different storage conditions for 24 hours and 30 days;

[0026] Figure 3 This is a comparison chart of the cumulative penetration of Bose;

[0027] Figure 4 This is a summary table of immunofluorescence results of active collagen type I. The images were taken using a fluorescence microscope (Olympus, BX43) at a magnification of 20×. Blue represents the cell nucleus, and green fluorescence represents active collagen type I. The stronger the green fluorescence intensity, the more active collagen type I content.

[0028] Figure 5 The bar graph is the relative integrated optical density (IOD) value of active collagen type I. When the t-test method was used for statistical analysis, compared with the BC group, the significance was indicated by #, P < 0.05 was indicated by #, and P < 0.01 was indicated by ##; compared with the NC group, the significance was indicated by *, P < 0.05 was indicated by *, and P < 0.01 was indicated by **; compared with honey-2%, the significance was indicated by ◆, P < 0.05 was indicated by ◆, and P < 0.01 was indicated by ◆◆;

[0029] Figure 6This is a summary table of the results of immunofluorescence of active collagen type IV; it was photographed under a fluorescence microscope (Olympus, BX43) at a magnification of 20×. Blue represents the cell nucleus, and green fluorescence represents active collagen type. The stronger the green fluorescence intensity, the more active collagen type content it represents.

[0030] Figure 7 It is a bar graph of the relative integrated optical density (IOD) / area mean of active collagen type IV. DETAILED DESCRIPTION

[0031] The present invention provides a glycoside derivative flexible liposome with moisturizing and anti-wrinkle functions, comprising a main shell material, a moisturizer, a wrapped raw material, an auxiliary shell material, a preservative and a solvent; the mass fractions of the above components are as follows:

[0032] Table 1 Composition range of glycoside derivative flexible liposomes

[0033]

[0034] The main shell material is any one or more of lecithin, phosphatidylserine and phosphatidylcholine.

[0035] The auxiliary shell material is polyquaternium-51.

[0036] The preservative is any one or more of 1,2-hexanediol, p-hydroxyacetophenone, methylparaben and caprylyl glycol.

[0037] The moisturizing agent is butylene glycol; the wrapped raw material is hydroxypropyl tetrahydrofurantriol; and the solvent is deionized water.

[0038] Table 2 Composition of Examples 1-3:

[0039]

[0040] The composition of Comparative Examples 1-6:

[0041] Comparative Example 1: No auxiliary shell material was added, and other components and contents were the same as those in Example 1;

[0042] Comparative Example 2: The auxiliary shell material is 1.0 mass percent of sodium di(lauroyl glutamine) lysine, and the other components and contents are the same as those in Example 1;

[0043] Comparative Example 3: The auxiliary shell material is 0.5 parts by weight of cholesterol and 0.5 parts by weight of ceramide, and the other components and contents are the same as those in Example 1;

[0044] Comparative Example 4: The auxiliary shell material is 1.0 mass percent of sodium polylysine, and the other components and contents are the same as those in Example 1;

[0045] Comparative Example 5-6: The ingredients and contents are the same as those in Example 1.

[0046] Preparation process of Examples 1-3 and Comparative Examples 1-6:

[0047] Example 1

[0048] Weigh the main shell material and moisturizer in proportion, heat and stir them in a 45-75℃ water bath, then add the wrapped raw material that has been preheated in a 45-75℃ water bath for 30 minutes, stir for 10 minutes to obtain a mixture A; preheat the auxiliary shell material and preservative in a 45-75℃ water bath for 30 minutes, then add them to the mixture A and continue stirring for 10 minutes until uniform to obtain a mixture B, then cool it to 35-45℃; then preheat it in a 35-45℃ water bath for 30 minutes n solvent is injected into mixture B at an injection rate of 1 g / min / 100 g total system. During the injection process, stirring is continued at a speed of 600-800 rpm. After the injection is completed, hydration is continued for 20 minutes to obtain colostrum. Finally, the colostrum is homogenized with a microfluidizer, the homogenization pressure is set to 14000 psi, the number of homogenization cycles is 3, the discharge temperature of the first homogenization is controlled to be 25°C, the discharge temperature of the second homogenization is controlled to be 20°C, and the discharge temperature of the third homogenization is controlled to be 15°C to obtain a material body.

[0049] Example 2

[0050] The preliminary preparation process is the same as that in Example 1. The homogenization pressure is set to 12000 psi during homogenization, the number of homogenization cycles is 3 times, the discharge temperature of the first homogenization is controlled to be 20°C, the discharge temperature of the second homogenization is controlled to be 15°C, and the discharge temperature of the third homogenization is controlled to be 10°C to prepare a material body.

[0051] Example 3

[0052] The preliminary preparation process is the same as that in Example 1. The homogenization pressure is set to 15000 psi during homogenization, the number of homogenization cycles is 3 times, the discharge temperature of the first homogenization is controlled to be 30°C, the discharge temperature of the second homogenization is controlled to be 25°C, and the discharge temperature of the third homogenization is controlled to be 20°C to prepare a material body.

[0053] Comparative Examples 1-4

[0054] The preparation process is the same as that in Example 1.

[0055] Comparative Example 5

[0056] The initial preparation process was the same as that in Example 1. During homogenization, the homogenization pressure was set to 10,000 psi, and the cycle was repeated 3 times without controlling the discharge temperature.

[0057] Comparative Example 6

[0058] The preliminary preparation process was the same as that in Example 1. During homogenization, the homogenization pressure was set to 15000 psi, and the cycle was repeated once. The discharge temperature was controlled at 30° C., and then the material was naturally cooled to obtain a material body.

[0059] Example 4

[0060] Stability performance test of Examples 1-3 and Comparative Examples 1-6

[0061] After the preparation of Examples 1-3 and Comparative Examples 1-6, appropriate amounts were taken and placed in a closed transparent container, and placed at -20°C, room temperature (25°C), 4°C, and 45°C for 3 months. Examples 1-3 were always yellowish transparent liquids without stratification and precipitation; Comparative Example 1 was a light blue transparent liquid, which darkened at high temperature after 3 months; Comparative Example 2 was initially a relatively transparent liquid, and precipitation occurred at high temperature and 4°C. The precipitate may be caused by the incompatibility of the amino acid surfactant and the bosin; Comparative Example 3 was initially a translucent liquid, which became turbid at all temperatures, which may be due to the poor solubility of ceramide Easy to self-crystallize; Comparative Examples 4-6 are all light blue transparent liquids. After 3 months, the transparency decreases at room temperature and high temperature. Comparative Example 4 may be unstable due to the high proportion of sodium polylysine. It is further measured that the initial average particle size of Comparative Example 5 is 54.82nm, and the dispersity index (PDI) is 0.393. The initial average particle size of Comparative Example 6 is 68.23nm, and the dispersity index (PDI) is 0.412. Comparative Examples 5 and 6 may be unstable due to insufficient homogenization pressure and the discharge temperature is not gradually cooled, resulting in large and uneven liposome particle sizes.

[0062] Example 5

[0063] Particle size, PDI and bosine content testing

[0064] The product of Example 1 (hereinafter replaced by "Meipuin") was prepared as a 1% aqueous dispersion and placed at room temperature for 24 hours for aging. After 24 hours, the appearance of the sample was preliminarily observed, and the particle size and PDI tests were performed.

[0065] The results are as follows Figure 1 As shown, the measured numerical average particle size of 1% concentration of mepurin is (23.25±0.80) nm, the PDI is 0.299, and the PDI<0.300, indicating that the mepurin prepared by the method of the present invention has a small particle size and a narrow particle size distribution, with an average diameter of 10.48 nm and a peak standard deviation of 3.25 nm. The flexible liposomes are uniform in size and have good stability.

[0066] Example 6

[0067] Stability test

[0068] Honeypurine was prepared as a 1% aqueous dispersion and aged at room temperature for 24 h. It was then stored at 45°C, 4°C, -20°C and room temperature (RT), respectively. The particle size, polydispersity index (PDI), pH and honeypurine content were tested after storage for 24 h and 30 days, and its appearance was observed.

[0069] The test was conducted using a 1% aqueous dispersion of honey, and the average particle size and PDI were tested using a nanoparticle size analyzer at room temperature. The pH value was tested using a 10% aqueous dispersion of honey, and the content of phosphine in honey was quantitatively analyzed using HPLC-ELSD.

[0070] The stability is evaluated by comprehensively considering product appearance, particle size (1% concentration dispersed liquid), dispersion (1% concentration dispersed liquid), pH change and change in phosphine content.

[0071] Table 3 Changes in particle size, PDI, pH and phosphine content of honeypurine under different storage conditions

[0072]

[0073] Depend on Figure 2 As can be seen from Table 3, the pH and phosphine content of the honey liposome in Example 1 were almost unchanged after storage at different temperatures for 30 days. After storage at 45°C for 30 days, the average particle size and PDI changed slightly, and the honey liposome was basically stable.

[0074] Example 7

[0075] Transdermal permeability test data

[0076] Transdermal penetration experiment of Mepurin

[0077] 1. Test method:

[0078] Experimental groups and sample configuration: Control group: Essence prepared by directly adding hydroxyethyl acrylate raw material to the base material (the hydroxyethyl acrylate content is 2.5%); Treatment group: Essence prepared by adding mepurin to the base material (the hydroxyethyl acrylate content is 2.5%); Essence base material formula: SIMULGEL FL (hydroxyethyl acrylate & sodium dimethyl taurate copolymer & isohexadecane & polysorbate 60) 0.8%, propylene glycol 3%, glycerin 3%, and water as the balance.

[0079] 2) Assembly and fixation of the test model: Fix the skin simulation membrane (Strat-M) between the diffusion chamber and the receiving chamber of the vertical Franz diffusion cell, with the rough surface of the skin simulation membrane facing the diffusion chamber and the smooth surface facing the receiving chamber. After fixing the skin simulation membrane, add 8 mL of receiving solution (7.4 PBS) to the receiving chamber to make the skin simulation membrane in close contact with the receiving solution.

[0080] 3) The static vertical transdermal diffusion cell was fixed in the transdermal diffusion instrument, the temperature was set to 32 and the speed of the magnetic stirring rotor was set to 600 rpm.

[0081] 4) Sample loading: After the water bath temperature of the diffusion instrument is constant, sample loading is performed. The sample addition amount is 0.1 g. The sample is added to the surface of the skin simulation membrane and spread evenly.

[0082] 5) Sample collection in the receiving pool: Take 300 μL of receiving solution at 2, 5, 8, and 12 hours respectively, and add fresh receiving solution to measure the concentration of boson in the receiving solution.

[0083] 6) Quantitative analysis of boson in the receiving solution was performed by HPLC-ELSD.

[0084] 7) Data analysis: The cumulative permeation amount of boson in the receiving solution is quantitatively calculated using the following formula:

[0085]

[0086] Where:

[0087] Q: Cumulative permeability per unit area, refers to the sample permeability per unit area in the cumulative time;

[0088] Cn: sample concentration at the nth sampling point; V: volume of receiving liquid in the receiving pool;

[0089] V0: volume of each sampling; A: area of ​​receiving pool.

[0090] The results are as follows Figure 3 As shown in the figure, after 5 hours of penetration, the cumulative penetration of honey Pu Yin was higher than that of the control group. After 12 hours of penetration, the cumulative penetration of honey Pu Yin sample was about 2.6 times the penetration of the control group.

[0091] Example 8

[0092] Test on the moisturizing and anti-wrinkle effect of Mi Pu Yin on human body

[0093] Thirteen subjects aged 28-55 years were selected. The left and right faces of the subjects were used as the control group and the sample group respectively. The subjects applied the product twice a day during the normal skin care process in the morning and evening for 28 days. Skin physiological indexes were tested before use and on the 14th and 28th days of use. The face was cleaned and dried before the test. After sitting in a constant temperature and humidity environment (21±1℃, 50±10%) for 30 minutes, the skin indexes of the left and right faces were tested respectively. The elasticity and firmness were tested with a skin elasticity tester (Cutometer®), the transepidermal water loss was tested with a skin surface water loss test probe (Tewameter®TM HEX), and the water content of the stratum corneum was tested with a skin moisture tester (Corneometer® CM825).

[0094] Essence water matrix composition: 1.0% Carbomer 940, 0.5% p-hydroxyacetophenone, 3.0% 1,2-hexanediol, 95.5% deionized water.

[0095] Control group: Mix 10 mL of 30% Bossagra original liquid and 90 mL of essence water base.

[0096] Sample group: Mix 10 mL of Honey Pu Yin and 90 mL of essence water base.

[0097] Table 4 The moisturizing and anti-wrinkle efficacy test of Mipuin and Bosin on human body

[0098]

[0099] The test results are shown in Table 4. Both the control group and the sample group had significant improvement effects on the four indicators tested, but the sample group's Honey Pu Yin essence showed more significant improvement effects on elasticity and firmness after 14 days of use. Honey Pu Yin has better anti-wrinkle and firming effects.

[0100] Example 9

[0101] Anti-wrinkle efficacy test of Mipuin

[0102] 1. Test methods

[0103] 1) Tissue processing: Freshly obtained skin tissue was immersed in 75% alcohol and washed for 30 seconds, and then washed three times with sterile PBS buffer. After washing, the skin was cut into 24 ± 2 mm 2 Place the tissue block with the epidermis facing up and the dermis facing down into a culture mold, then transfer the culture mold into a 6-well plate, add 3.7 mL of culture medium to each well, and culture in a 37°C, 5% CO2 incubator, changing the medium every day.

[0104] 2) Administration: After 2 days of in vitro skin tissue culture, irradiation and administration were started according to the test groups and corresponding treatment conditions in the table; the irradiation dose was UVA (30J / cm 2 ) and UVB (50mJ / cm 2 ), irradiated continuously for 4 days, replaced with fresh culture medium after each irradiation, and drug administration was performed. PC (VC+VE) was administered submerged, and the sample to be tested was administered on the surface. After 4 days of continuous irradiation, the ex vivo skin tissue was cultured for another 3 days, during which no irradiation was performed, and only sample administration was performed.

[0105] 3) Immunofluorescence test: The skin tissue for detection was fixed with 4% paraformaldehyde for 24 hours, and then immunofluorescence detection was performed. Pictures were taken under a fluorescence microscope, and the images were collected and analyzed.

[0106] 4) Calculation of improvement rate: Improvement rate = (sample group - negative control group) / negative control group × 100%.

[0107] 5) Statistical analysis of results: GraphPad Prism software was used to draw graphs, and the results were expressed as mean ± standard deviation. The t-test was used for statistical analysis of the comparisons among the groups. All statistical analyses were two-tailed. P < 0.05 was considered to be significantly different, and P < 0.01 was considered to be extremely significantly different.

[0108] Table 5 Test groups

[0109]

[0110] The experimental results are as follows Figures 4 to 7 As shown in Table 5, compared with the BC group, the active collagen type I content of the NC group decreased significantly, indicating that the stimulation conditions of this test were effective. Compared with the NC group, the active collagen type I content of the PC group increased significantly, indicating that the positive control of this test was effective. Compared with the NC group, the active collagen type I content of the samples Mi Pu Yin-2% and Mi Pu Yin-10% increased significantly, with the increase rates of 80.65% and 283.87%, respectively. Compared with the BC group, the active collagen type IV content of the NC group decreased significantly, indicating that the stimulation conditions of this test were effective. Compared with the NC group, the active collagen type IV content of the PC group increased significantly, indicating that the positive control of this test was effective. Compared with the NC group, the active collagen type IV content of the samples Mi Pu Yin-2% and Mi Pu Yin-10% increased significantly, with the increase rates of 109.38% and 134.38%, respectively.

Claims

1. A method for preparing a glycoside derivative flexible liposome, characterized in that: The glycoside derivative flexible liposome comprises a main shell material, a moisturizing agent, a wrapped raw material, an auxiliary shell material, a preservative and a solvent; the main shell material is phosphatidylcholine; the auxiliary shell material is polyquaternium-51; the preservative is any one or more of 1,2-hexanediol, p-hydroxyacetophenone, methylparaben, phenoxyethanol and caprylyl glycol; the moisturizing agent is butylene glycol; the wrapped raw material is hydroxypropyl tetrahydrofurantriol; and the solvent is deionized water; The preparation method comprises the following steps: heating the main shell material and the moisturizing agent to 45-75°C in a water bath and stirring evenly; then adding the wrapped raw material preheated to the same temperature and stirring evenly to obtain a mixture A; preheating the auxiliary shell material and the preservative to the same temperature, then adding them into the mixture A and continuously stirring to obtain a mixture B; after cooling, injecting the solvent into the mixture B, and continuously hydrating after the injection to obtain colostrum; homogenizing the colostrum to obtain a glycoside derivative flexible liposome, wherein the particle size of the glycoside derivative flexible liposome is 10-40nm; controlling the discharge temperature of the first homogenization to be 20-30°C, the discharge temperature of the second homogenization to be 15-25°C, and the discharge temperature of the third homogenization to be 10-20°C.

2. The method for preparing the glycoside derivative flexible liposome according to claim 1, characterized in that: The glycoside derivative flexible liposome comprises the following components in parts by weight: 2-8 parts of a main shell material, 6-14 parts of a moisturizer, 25-35 parts of a wrapped raw material, 0.3-3 parts of an auxiliary shell material, 1-2 parts of a preservative and 38-65.7 parts of a solvent.

3. The method for preparing the glycoside derivative flexible liposome according to claim 1, characterized in that: After obtaining the mixture B, the temperature is lowered to 35-45°C; and the solvent preheated to 35-45°C is injected into the mixture B.

4. The method for preparing the glycoside derivative flexible liposome according to claim 1, characterized in that: The discharge temperature of the first homogenization pass was controlled at 25°C, the discharge temperature of the second homogenization pass was controlled at 20°C, and the discharge temperature of the third homogenization pass was controlled at 15°C.

5. The method for preparing the glycoside derivative flexible liposome according to claim 1, characterized in that: During the process of injecting the solvent into the mixture B, stirring is continued at a speed of 600-800 rpm. After the injection is completed, hydration is continued for 15-25 minutes to obtain colostrum.

6. The method for preparing the glycoside derivative flexible liposome according to claim 1, characterized in that: The colostrum was homogenized using a high pressure homogenizer, the homogenization pressure was set to 12000-15000 psi, and the number of homogenization cycles was 3 times.

7. A glycoside derivative flexible liposome, characterized in that: Prepared by the method according to any one of claims 1 to 6.

8. Use of the glycoside derivative flexible liposome according to claim 7 in personal care products.

9. The use according to claim 8, characterized in that: The personal care product is a skin care product.

10. The use according to claim 8, characterized in that: The mass percentage of the glycoside derivative flexible liposome in the personal care product is 1-3%.

Citation Information

Patent Citations

  • Cationic nano emulsion with anti-allergic effect and preparation method of cationic nano emulsion

    CN104784074A

  • Nanoemulsion preparation method for increasing bioavailability of pro-xylane

    CN111671662A

  • Nano-liposome composition with skin whitening and freckle removing effects as well as preparation method and application of nano-liposome composition

    CN116035980A

  • Encapsulated salicylic acid derivative as well as preparation method and application thereof

    CN116549329A

  • Preparation method and application of high-stability repair anti-aging liposome

    CN117942270A

Cited By

  • Preparation method and application of coated glass pigment

    CN119857055A

  • A preparation process of synthetic liposome for improving stratum corneum-dermis permeability

    CN122786213A